Approach to lymphadenopathy: how to diagnose tuberculosis lymphadenitis - Tanisha; Melnychuk , Iryna; Sharayeva , Maryna (The Ukrainian Scientific Medical Youth Journal, 2023)
lymphadenopathy is considered as abnormal finding local or generalized that can be caused by neoplasm or infection, as tuberculosis lymphadenitis. Cervical localization has prevalence in the variety of disorders, can has a similar kind of clinical presentation and to differentiate them becomes extremely difficult. We provided a case report of the new onset of extrapulmonary tuberculosis lymphadenitis in 42-year-old Indian man. The patient complained of multiply enlarged painful lymph nodes on left anterior neck and was also concerned about sore throat persistent for a year. Objective examination and analysis were without evident inflammatory signs. Previous ultrasound, pulmonary and abdominal CT-scan investigations also revealed conglomerate of left mediastinal lymph nodes, moderate splenomegaly. The preliminary diagnosis of lymphoma was excluded due to confirmation of typical tuberculosis lymphadenitis with specific testing and morphological changes of the resected lymphatic node. Sputum microscopy was found to be negative, which meant that the patient was negative for social transmission of tuberculosis. Affected lymph nodes resolved completely after appropriate therapy during one-year treatment. This case report of extrapulmonary tuberculosis highlights the importance of tissue diagnosis in unclear situations. We used clinical protocol for unspecified lymph node enlargement as complete history taking and physical examination that is preliminary for diagnosis, while laboratory tests, imaging diagnostic methods and tissue samplings are gold standard evaluation for definite lymphadenopathy. Tuberculosis lymphadenitis is popularly known as collar stud abscess and is the most common benign cause of cervical lymphadenopathy in endemic areas. This observation determined the details of the immunocompromised state of the patient, conclusion was supported by the evidence of Pseudomonas putida associated pharyngitis. The main differential signs between lymphoma as immunoproliferative disorder and infectious tuberculosis lymphadenitis were provided.